2021
DOI: 10.1590/1980-549720210019.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Survival time and distance to access specialized treatment among people living with HIV/Aids in the state of Alagoas, Brazil

Abstract: Objective: To evaluate the effect of the distance between the place of residence and the specialized treatment service on the survival time of people living with HIV/Aids in Alagoas, Northeast Brazil. Methods: Data from the notification and mortality systems related to individuals aged 13 years or older diagnosed with the infection between 2007 and 2013 were used. The cases were observed for a period of follow-up until December 2017. For the analyses, the Pearson's χ2 test, Kaplan-Meier method, and Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Another important element is the users' time since ART initiation, with individuals who started their treatment immediately after the notification of the first HIV/AIDS cases in Brazil. A Brazilian cohort study estimated a mean survival of 5 months for cases diagnosed in the 1980s, 18 months for those diagnosed in 1995 and 58 months for those diagnosed in 1996, whereas a study carried out in 2021 in the state of Alagoas revealed a median survival of 98 months [17][18] . The increase in PLWHIV survival over the years can be related to the HIV diagnosis expansion, to rapid ART initiation, and to the high effectiveness of the therapeutic regimens 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important element is the users' time since ART initiation, with individuals who started their treatment immediately after the notification of the first HIV/AIDS cases in Brazil. A Brazilian cohort study estimated a mean survival of 5 months for cases diagnosed in the 1980s, 18 months for those diagnosed in 1995 and 58 months for those diagnosed in 1996, whereas a study carried out in 2021 in the state of Alagoas revealed a median survival of 98 months [17][18] . The increase in PLWHIV survival over the years can be related to the HIV diagnosis expansion, to rapid ART initiation, and to the high effectiveness of the therapeutic regimens 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Some municipalities with large PHC investments and structuring, such as Curitiba and Rio de Janeiro, effectively started to decentralize the care provided to PLWHIV to basic care services. This has enabled PHC to provide services that were previously only seen at the secondary and tertiary levels 17,28 .…”
Section: Rbfhssmentioning
confidence: 99%
“…The interference of geographic access, distance and commute from the patient’s home to the health service is a major obstacle, especially as a result of the service offered to people living with HIV/AIDS being centralized in a single physical space ( 23 ) . It is important to consider that, along the geographic route, some subjects need a longer period of time to commute to the specialized care service and, consequently, face greater accessibility obstacles for care and access to ART ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…La interferencia del acceso geográfico, la distancia y el desplazamiento desde la residencia del paciente hasta el servicio de salud es un obstáculo importante, especialmente porque el servicio ofrecido a las personas que viven con VIH/sida está centralizado en un único espacio físico (23) . Es importante considerar que, durante el recorrido geográfico, algunos necesitan más tiempo para desplazarse hasta el servicio de atención especializada y, en consecuencia, se enfrentan a mayores obstáculos de accesibilidad a la atención y de acceso al TAR (9) .…”
Section: Abandonounclassified
“…Cabe destacar que el acceso al servicio de atención sanitaria especializada es un factor que influye en la adherencia a los cuidados en VIH/sida y TAR, especialmente para su cronicidad. Así, la falta de integración con otros servicios sanitarios, especialmente los integrados en atención primaria, asociada a la centralización de la atención especializada, puede favorecer la fragmentación del desarrollo de acciones y estrategias de promoción y prevención de la salud (23) .…”
Section: Abandonounclassified